CD26 Inhibition Potentiates the Therapeutic Effects of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells by Delaying Cellular Senescence - Kim, Miyeon; Go, Jinyoung; Kwon, Ji Hye; Jin, Hye Jin; Bae, Yun Kyung; Kim, Eun-Young; Chang, Eun-Ju; Choi, Soo Jin; Kim, Seong Who (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) are recognized as potential treatments for multiple degenerative and inflammatory disorders as a number of animal and human studies have indicated their therapeutic effects. There are also several clinically approved medicinal products that are manufactured using these cells. For such large-scale manufacturing requirements, the in vitro expansion of harvested MSCs is essential. Multiple subculturing of MSCs, however, provokes cellular senescence processes which is known to deteriorate the therapeutic efficacy of the cells. Strategies to rejuvenate or selectively remove senescent MSCs are therefore highly desirable for fostering future clinical applications of these cells. In this present study, we investigated gene expression changes related to cellular senescence of MSCs derived from umbilical cord blood and found that CD26, also known as DPP4, is significantly upregulated upon cellular aging. We further observed that the inhibition of CD26 by genetic or pharmacologic means delayed the cellular aging of MSCs with their multiple passaging in culture. Moreover, the sorting and exclusion of CD26-positive MSCs from heterogenous cell population enhanced in vitro cell attachment and reduced senescence-associated cytokine secretion. CD26-negative MSCs also showed superior therapeutic efficacy in mouse lung emphysema model. Our present results collectively suggest CD26 is a potential novel target for the rejuvenation of senescent MSCs for their use in manufacturing MSC-based applications.